Marrying the Unbeliever: Gender, Law, and Disparitas Cultus in Early Modern Japan*. - de Oliveira Coutinho Silva, Luisa Stella (Journal of Religious History, 2025)
The marriage between a Christian and a non‐Christian has been a highly discussed topic in the history of the Catholic Church and canon law. This study aims to analyse the construction of knowledge concerning disparitas cultus by using a broad array of sources including moral theology, canon law, and missionaries' cases that circulated in different regions of the Iberian Empires. It examines theoretical discussions by theologians in Japan and other parts of the Iberian Empires, as well as case studies described by missionaries in Japan involving Japanese Christians married to non‐Christians. The focus lies on revealing the arguments used both for and against marriage with disparity of cults, and on demonstrating the existence of diverse arrangements of marital cohabitation beyond the theoretical debates held on by scholars in Europe and Asia. From the perspective of women's legal history, it explores the relativisation of paternal consent, religious beliefs and social practices of cohabitation, gender roles within such relationships, household compositions and human relations, all contributing to the numerous situations in which couples live in disparitas cultus. Lastly, this article showcases how missionaries' sources can offer fresh interpretations to women's history in sixteenth and seventeenth‐century Japan.